PENGEMBANGAN PENDIDIKAN BERBASIS KEUNGGULAN BUDAYA LOKAL UNTUK MENINGKATKAN PRESTASI BELAJAR MAHASISWA - Dhiniaty Gularso dan Rosalia Susila Purwanti (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
The purpose of this study is students can explore the local culture or indigenous wisdom-basedinquiry learning culture through the Regional Cultural Education courses to be included in the syllabusand lesson plans for each subject to elementary school. Syllabus and lesson plans based on the indigenousculture is expected to foster respect and appreciate the diversity of Indonesian culture. The method usedin this research is the development of research berpendekatan Research and Development which refers toThiaragajan (1994) with 4D models that define, design, develop and disseminate. The data required in thisresearch is quantitative data and qualitative data. Analysis of the data in this study is a descriptivequalitative. The results of this study are to the average of 78.7 while 81.0 masksimal value and aminimum value of 76.7 These results prove that proves that the research is successful because of thesuccess criteria of this study was 75. Based on these results it can be concluded that the development ofeducation-based advantage of local culture can be used as learning models Regional Cultural Educationcourses to enhance the achievement of students.